Surface roughness and roundness optimization on turning process of Aluminium Alloy with Taguchi Method / Sudjatmiko … [et al.] - Sudjatmiko, djatmiko. mlg@gmail. com; Soenoko, Rudy; Suprapto, Agus; Choiron, Moch. Agus (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this study, surface roughness and roundness were established as process parameters on turning process of Aluminium Alloy by using Taguchi Method. Taguchi design of experiments (DOE) is used to analyze the effect of each parameters design. The four parameters are nose radius (nr), spindle speed (n), depth of cut (a) and feeding (f). The observed value is denoted by using surface roughness and roundness. From this result, it can be concluded that the optimum design based on surface roughness is chosen as optimum turning process parameter for this study. It can be found that nr have stronger influence on the observed value. The optimum design is a product with nr = 1.2 mm, n = 1000 rpm, a = 0.25 and f = 0.056 mm based on surface roughness evaluation.